Immune response to heavy exertion - Nieman, D. C. (Journal of Applied Physiology, 1997)
Epidemiological data suggest that endurance athletes are at increased risk for upper respiratory tract infection during periods of heavy training and the 1- to 2-wk period following race events. There is growing evidence that, for several hours subsequent to heavy exertion, several components of both the innate (e.g., natural killer cell activity and neutrophil oxidative burst activity) and adaptive (e.g., T and B cell function) immune system exhibit suppressed function. At the same time, plasma pro- and anti-inflammatory cytokines are elevated, in particular interleukin-6- and interleukin-1-receptor antagonist. Various mechanisms explaining the altered immunity have been explored, including hormone-induced trafficking of immune cells and the direct influence of stress hormones, prostaglandin-E2, cytokines, and other factors. The immune response to heavy exertion is transient, and further research on the mechanisms underlying the immune response to prolonged and intensive endurance exercise is necessary before meaningful clinical applications can be drawn. Some attempts have been made through chemical or nutritional means (e.g., indomethacin, glutamine, vitamin C, and carbohydrate supplementation) to attenuate immune changes following intensive exercise.